Proposal for improvement of production process in a company that produces PVC fittings through thermoforming using dmaic improvement cycle - Matsuoka Diaz, Javier Shigeki (2016)
The purpose for this paper is to reduce production losses at a PVC fitting manufacturer by using as a tool for improvement the DMAIC improvement cycle. Define (D), Measure (M), Analyze (A), Improve (I) and Control (C) are the phases that will be applied with the support of statistical tools to develop a solution. For the diagnosis of the current situation of the company, the first 3 phases of DMAIC improvement cycle were used. The Define phase (D), identifies the main problem by a matrix that considers several factors such as frequency, monthly losses and ease of implementation. In this manner, high shrinkage is selected as the main problem of the company. Also, the scope of the project is determined by the Project Charter. In the Measure phase (M), the current situation of the company is described. The economic impact is assessed by reduced production and the products are classified by families identifying those families who have most participation. VSM analysis was done to examine the characteristics of each of the sub process identified. To make the process capability analysis, a representative sample was taken and then the indicators are calculated. In the Analyze phase (A), the cause and effect diagram was performed to identify possible causes of the problem. The qualitative information was transferred to quantitative using a Pareto chart. Likewise, correlation assumptions were raised between time and temperature. For the evaluation of the proposed improvement, the phase Improved was used. In the Improve phase (I), proposals for cutting and thermoforming processes were performed. For the cutting process using supports, side latches and up-and-down cutting blade. In the thermoforming process, using an ovenproof and a system for automated control of the gas flow to the correct temperature measurement is proposed. All the above goes along with a procedure. For the evaluation of the results, the Control phase was used. In the Control phase (C), an ovenproof prototype was performed and testing to obtain the time when the pipe gain flexibility while it’s working with VICAT Temperature (80 °C). The test concluded in 23 seconds on average. A sample sections were used to verify the new capability index. The information collected was used to simulate how works the improvements in the time and using Arena software make sure the effectiveness of the improvement. It’s estimated to reduce from 12% to 6% of production losses, which it’s the main goal of the project. The financial analysis indicates the investment is profitable. The owner should perform the implementation.